Waiting to learn : an analysis of instruction in four preschool settings in poor contexts - Jowell, Justin (School of Education, 2016)
Worldwide there has been a growing recognition of the important role that preschool education can play in supporting later school (and life) success. At the school level, studies that examine and broaden knowledge of educational transmission in the classroom (pedagogic discourse) have been useful in providing pointers towards better practices to support children's learning at school. Extending the study of pedagogy to the preschool level seems to hold great potential for better understanding how to support children's learning. This study, based within a sociology of education framework, poses the question: How is pedagogy constituted and how does it vary across four different preschools situated in working class areas? Using a case study approach, four sites were chosen from the same setting, and classroom observation data collected. The study examines in these sites how time is distributed across the school day in relation to different domains of early learning; how pedagogy is structured (and how it varies); and how what is offered at the four settings compares to an optimal1 pedagogy identified for school, and preschool, in the research literature. Drawing on Basil Bernstein's conceptual frame for the analysis of pedagogy, a coding tool was adapted from Hoadley (2005) for the preschool setting which enabled a robust description and comparison of the pedagogy at the four sites.